The supply side of discrimination: Evidence from the labor supply of Boston taxi drivers - Osborne Jackson (Federal Reserve Bank of Boston, 2018)
This paper investigates supply-side discrimination in the labor market for Boston taxi drivers. Using data on millions of trips from 2010-2015, I explore whether the labor supply behavior of taxi drivers differs by the gender, racial/ethnic, or age composition of Boston neighborhoods. I find that disparities in shift hours due to neighborhood demographics exist even when differences in local earnings opportunities are taken into account. I observe heterogeneity in the amount that drivers discriminate and find that this discrimination is primarily statistical rather than taste-based. As drivers gain experience and learn to better anticipate wage variation, discrimination decreases.
Keywords: J71; J22; J31; L91; 330; discrimination; labor supply; Boston taxis; wage elasticity